Epidemiological and virological surveillance of the prevention of mother-to-child transmission of HIV among pregnant women in Togo - Kokou Tegueni; Fifonsi Adjidossi Gbeasor-Komlanvi; Oumarou I. Wone Adama; Arnold Junior Sadio; Amivi Phyllis Amenyah-Ehlan; Claver Anoumou Dagnra; Didier Koumavi Ekouevi (BMC, 2024)
Summary Background In 2015, Togo introduced the "test-and-treat" strategy for the prevention of mother-to-child transmission (PMTCT) of HIV. Pediatric HIV infection remains a public health problem in Togo, with a mother-to-child transmission (MTCT) rate of 3.6% in 2020. This study aimed to estimate cases of HIV seroconversion during pregnancy and to identify pregnant women at high risk of transmitting HIV to their children in Lomé, Togo. Methods A descriptive cross-sectional study was carried out from 18 March to 22 May 2022 among women who had given birth in five maternity units providing PMTCT services in Lomé. Umbilical cord blood samples were taken from the maternal side by midwives after delivery. HIV serology was performed in the laboratory using the Alere™ HIV Combo SET and First Response HIV 1-2. Card Test version 2.0. A sample was considered positive if both tests were positive. The HIV-1 viral load in HIV-1-positive samples was measured using Cobas/Roche 4800 equipment. Information on the women was extracted from maternal antenatal records and antenatal consultation registers. Results A total of 3148 umbilical cord blood samples (median maternal age: 28 years (interquartile range [24-32]) were collected. Among them, 99.3% (3145/3148) had presented for at least one antenatal clinic visit before giving birth, and 78.7% (2456/3122) had presented for at least four visits. One hundred and twenty-one (121) cord samples were HIV-1 positive, representing a seroprevalence of 3.8% (95% CI = [3.2-4.6]). Among them, 67.8% (82/121) were known HIV-positive before the current pregnancy, 29.7 (36/121) were diagnosed as HIV-positive at the antenatal visits and 2.5% (3/121) were diagnosed as HIV-positive in the delivery room. Of the HIV-positive women, 85.9% (104/121) were on ARV treatment before delivery. The viral load was < 1000 copies/ml in 97.5% (118/121) cases. Conclusion This study explored the virologic and epidemiological aspects of HIV among pregnant women in Togo. The results show significant viral suppression at delivery in women ART. Surveillance based on umbilical cord blood specimen screening is an interesting approach for monitoring the effectiveness of PMTCT programmes.